Between Text and Law: Hasan Al-Turabi's Interpretation of Dilalah Lafz Al-Ahkam in Marital Prohibition Verses - Fakih Abdul Azis; Siti Khadijah; Basyir Arif (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study offers a critical analysis of the Dilalah Lafz ala al-Ahkam method (verbal indication of legal rulings) as conceptualized by Hasan al-Turabi, with particular emphasis on his interpretive approach to Qur’anic injunctions concerning prohibited forms of marriage. Employing a qualitative, library-based research methodology, this paper adopts a descriptive-analytical framework and draws primarily from al-Tafsir al-Tawhidi as the central textual source. The theoretical underpinning is grounded in the framework of mantuq and mafhum—a methodological apparatus developed by Khalid Ibn Uthman al-Sabt for legal hermeneutics within the Dilalah Lafz tradition. The analysis proceeds by identifying and cataloguing relevant Qur’anic verses addressing prohibited marriages, explicating al-Turabi’s hermeneutical approach, and subsequently assessing it through the lens of mantuq and mafhum theory. The findings suggest that al-Turabi’s interpretative method is consistent with the analytical strategies of the Mutakallimin school, especially in his reliance on explicit (mantuq) and implicit (mafhum) textual meanings to derive legal rulings.